What is Sharia Based Hotel? A Meta-Analysis - Aam Rusydiana; Lina Nugraha Rani (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2021)
This study tries to review the research around Sharia compliance hotel on reputable journal. It uses descriptive statistical analysis based on selected 50 article publications or paper related to sharia compliance hotel, with national and international journal. The entire sample journal publications have published for 7 years from 2013 to 2020. The Results show that sharia compliance hotel research study case is still dominated by Malaysia (29%), following by Indonesia (20%). There are at least 42 journals that publish sharia compliance hotel articles and the most research with Journal of Global Business and Social Entrepreneurship (GBSE), International Journal of Academic Research in Business and Social Sciences, Australasian Journal of Islamic Finance and Business, International Journal of Islamic Marketing and Branding, Journal of Islamic Monetary Economics and Finance Furthermore, the comparison of qualitative research (58%) is still more than the quantitative approach (42%).